A transgenic bacterial artificial chromosome approach to identify regulatory regions that direct Amhr2 and Osterix expression in Müllerian duct mesenchyme - Moses, Malcolm M.; Mullen, Rachel D.; Idowu, Daniel I.; Maye, Peter; Jamin, Soazik P.; Behringer, Richard R. (Frontiers in Cell and Developmental Biology, 2022)
Transcriptional enhancers that direct Müllerian duct-specific expression have not been identified. Amhr2 encodes the receptor that mediates anti-Müllerian hormone (AMH) signaling for Müllerian duct regression in male embryos. Amhr2 is expressed in the Müllerian duct mesenchyme of both male and female embryos. A ~147-kb bacterial artificial chromosome (BAC) clone containing the Amhr2 locus was used to generate transgenic mice. The transgene was able to rescue the block in Müllerian duct regression of Amhr2-null males, suggesting that the BAC clone contains a Müllerian duct mesenchyme transcriptional enhancer active in male embryos. Osterix (Osx, also known as Sp7) is an AMH-induced gene that is also expressed in the Müllerian duct mesenchyme but only in male embryos. Osx-Cre transgenic mice were previously generated using a ~204-kb BAC clone. Crosses of Osx-Cre mice to Cre-dependent lacZ reporter mice resulted in reporter expression specifically in the Müllerian duct mesenchyme of male but not female embryos. Osx-Cherry transgenic mice were previously generated using a 39-kb genomic region surrounding the Osx locus. We found that Osx-Cherry embryos expressed red fluorescence in the Müllerian duct mesenchyme of male but not female embryos. In addition, female Osx-Cherry embryos ectopically expressing human AMH from an Mt1-AMH transgene activated red fluorescence in the Müllerian duct mesenchyme. These results suggest that the 39-kb region used to generate Osx-Cherry contains a male-specific Müllerian duct mesenchyme enhancer that is responsive to AMH signaling. These BAC transgenic mouse approaches identify two distinct enhancers that direct Müllerian duct transcription during sex differentiation.